2019
DOI: 10.1016/j.aim.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Associative Yang–Baxter equation and Fukaya categories of square-tiled surfaces

Abstract: We show that all strongly non-degenerate trigonometric solutions of the associative Yang-Baxter equation (AYBE) can be obtained from triple Massey products in the Fukaya categories of square-tiled surfaces. Along the way, we give a classification result for cyclic A ∞ -algebra structures on a certain Frobenius algebra associated with a pair of 1-spherical objects in terms of the equivalence classes of the corresponding solutions of the AYBE. As an application, combining our results with homological mirror symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…It follows from the analysis made by Schedler [27] that not every quasi-constant (quasi-)trigonometric solutions of CYBE for the Lie algebra sl n (C) can be lifted to a solution of the associative Yang-Baxter equation for Mat n×n (C). Therefore, the combinatorial patterns of the trigonometric solutions of CYBE for sl n (C) (see [4]), of the quasi-trigonometric solutions of the CYBE for sl n (C) (see [21,26]) and of the trigonometric solutions of the AYBE for Mat n×n (C) (see [25,22]) share similar features but are different.…”
Section: On Quasi-trigonometric Solutions Of Cybementioning
confidence: 99%
See 1 more Smart Citation
“…It follows from the analysis made by Schedler [27] that not every quasi-constant (quasi-)trigonometric solutions of CYBE for the Lie algebra sl n (C) can be lifted to a solution of the associative Yang-Baxter equation for Mat n×n (C). Therefore, the combinatorial patterns of the trigonometric solutions of CYBE for sl n (C) (see [4]), of the quasi-trigonometric solutions of the CYBE for sl n (C) (see [21,26]) and of the trigonometric solutions of the AYBE for Mat n×n (C) (see [25,22]) share similar features but are different.…”
Section: On Quasi-trigonometric Solutions Of Cybementioning
confidence: 99%
“…In the light of the work [11], it is natural to expect that any trigonometric solution of the CYBE arises as the geometric r-matrix of a pair (E, A), where E is a nodal Weierstraß cubic (such realizability is known for all elliptic and rational solutions; see [11] and references therein). On the other hand, the appearance of the Fukaya categories of higher genus Riemann surfaces in the classification of trigonometric solutions of AYBE [22] indicates, that a geometrization of the trigonometric solutions of CYBE could lead to further surprises.…”
Section: On Quasi-trigonometric Solutions Of Cybementioning
confidence: 99%
“…In the above form the AYBE was introduced in [11]; the constant version was introduced in [1]. In [12] we proved an analog of Belavin-Drinfeld classifications for nondegenerate skew-symmetric solutions of the AYBE for the matrix algebra Mat n (C) in terms of some combinatorial data, called associative Belavin-Drinfeld data (BD data) (for the definition of the nondegeneracy condition, which is stronger than the one for the CYBE, see [10,Def. 1.4.3]).…”
Section: Introductionmentioning
confidence: 96%
“…In [12] we showed that some of trigonometric solutions of the AYBE are realized geometrically using families of 1-spherical objects (V s ), (O x ) on some nodal Calabi-Yau curves, where V s are simple vector bundles. In [10] we realized all nondegenerate trigonometric solutions of the AYBE using objects in the Fukaya categories of square-tiled surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the description of simple vector bundles on Kodaira cycles of projective lines given in [15], Polishchuk computed the corresponding trigonometric solutions of AYBE [40]. Recently, Lekili and Polishchuk realized all trigonometric solutions of AYBE in terms of certain triple Massey products in the Fukaya category of an appropriate punctured Riemann surface [34].…”
Section: Introductionmentioning
confidence: 99%